Curriculum Change in Nunavut: Towards Inuit Qaujimajatuqangit - McGregor, Heather (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2012)
Between 1985 and the present, curriculum developers, educators and Elders in Nunavut have been working towards reconceptualization of curriculum to better meet the strengths and needs of Inuit students and to reflect, preserve, and revitalize Inuit worldview, language, and culture. This article outlines the development of the 1989 curriculum framework Piniaqtavut, the 1996 framework Inuuqatigiit: The Curriculum from the Inuit Perspective, and the 2007 foundation document Inuit Qaujimajatuqangit: Education Framework for Nunavut Curriculum. It goes on to describe the cross-curricular principles and philosophies of education in Nunavut, and identify the most important contributing factors in this system-wide curriculum change process. The intent is both to describe the approach taken in Nunavut, as well as to inform comparable work in other Indigenous contexts.